2015
DOI: 10.1095/biolreprod.115.131276
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Identity in the Absence of Pro-Testis Factor SOX9 and Pro-Ovary Factor Beta-Catenin in Mice1

Abstract: Sex-reversal cases in humans and genetic models in mice have revealed that the fate of the bipotential gonad hinges upon the balance between pro-testis SOX9 and pro-ovary beta-catenin pathways. Our central query was: if SOX9 and beta-catenin define the gonad's identity, then what do the gonads become when both factors are absent? To answer this question, we developed mouse models that lack either Sox9, beta-catenin, or both in the somatic cells of the fetal gonads and examined the morphological outcomes and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 50 publications
7
65
1
Order By: Relevance
“…Such redundancy is a common theme in our understanding of sex determination. Similar observations have been made in embryonic gonads lacking Sox9 and Ctnnb1 (Nicol and Yao 2015) and Fgf9 and Wnt4 (Jameson et al 2012a). One intriguing question remains after these observations, namely, why does the removal of two key testis-and ovary-determining genes result in a tendency toward testis development, given the initial ovarian lineage priming that exists in the bipotential gonad?…”
Section: Probing the Antagonism Between The Testisand Ovary-determinisupporting
confidence: 64%
See 1 more Smart Citation
“…Such redundancy is a common theme in our understanding of sex determination. Similar observations have been made in embryonic gonads lacking Sox9 and Ctnnb1 (Nicol and Yao 2015) and Fgf9 and Wnt4 (Jameson et al 2012a). One intriguing question remains after these observations, namely, why does the removal of two key testis-and ovary-determining genes result in a tendency toward testis development, given the initial ovarian lineage priming that exists in the bipotential gonad?…”
Section: Probing the Antagonism Between The Testisand Ovary-determinisupporting
confidence: 64%
“…Consistent with their roles in ovary development, Rspo1 and Wnt4 transcripts are detected in the bipotential gonad of XY and XX embryos; their expression persists in the XX gonad after 11.5 dpc but is lost from the XY gonad at the same stage (Auguste et al 2011;Bouma et al 2010;Jameson et al 2012b;Nef et al 2005;Parma et al 2006;Vainio et al 1999). Deletion of Rspo1, Wnt4, or Ctnnb1 results in similar gonadal phenotypes, characterized by partial female-to-male sex reversal, including ectopic migration of mesonephric endothelial cells leading to development of a testis-like coelomic vessel, ectopic migration of steroidogenic cell precursors from the adrenal glands inducing androgen production, and, in the case of loss of Rspo1 and Wnt4, transdifferentiation of some granulosa cells into Sertoli-like cells expressing Sox9 and formation of testis cords around the time of birth (Chassot et al 2008;Heikkila et al 2002;Jeays-Ward et al 2003Liu et al 2009;Maatouk et al 2008;Manuylov et al 2008;Nicol and Yao 2015;Tomizuka et al 2008;Vainio et al 1999). Follistatin (Fst) and bone morphogenetic protein 2 (Bmp2), both of which exhibit enhanced expression in the XX gonad after 11.5 dpc, have been identified as targets of the WNT signaling pathway during ovarian development.…”
Section: Granulosa Cells and The Rspo1/wnt/β-catenin Signaling Pathwaymentioning
confidence: 56%
“…For example, SRY and SOX9 [Li et al, 2014], as well as SOX9, SOX8, and SOX10 [Schepers et al, 2003;Polanco et al, 2010] have been shown to activate similar target genes. Accordingly, the masculinization of Sox9 /β-catenin double knockout XY gonads was associated with the expression of Sry and Sox8 [Nicol and Yao, 2015]. In contrast, for the expression of ovarian-specific genes the activation by the β-catenin pathway is absolutely essential.…”
Section: Cross-talk Between the Testicular And Ovarian Pathway Of Genmentioning
confidence: 98%
“…Interestingly, double knockout studies involving the combination of male-and female-determining pathways such as Wnt4 and Fgf9 or Wnt4 and Fgfr2 [Jameson et al, 2012], Rspo1 and Sox9 [Lavery et al, 2012], or Ctnnb1 (β-catenin) and Sox9 [Nicol and Yao, 2015] rescued the male-to-female sex reversal phenotype in XY gonads of the single knockout of Sox9 , Fgf9 , or Fgfr2 . In contrast in XX gonads, the partial female-to-male sex reversal of the single knockout of Wnt4 , Rspo1, or Ctnnb1 was not res-cued in the double-knockout gonads.…”
Section: Cross-talk Between the Testicular And Ovarian Pathway Of Genmentioning
confidence: 99%
“…Two key factors secreted by the ovary, wingless-type MMTV integration site family member 4 (WNT4) and R-spondin homolog RSPO1, a ligand of the LGR5 receptor that regulates the WNT/ CTNNB1 (β-catenin) signaling pathway [Carmon et al, 2011;de Lau et al, 2011], synergistically regulate the thickening of the coelomic epithelium and its subsequent expansion toward the subepithelial region in both XY and XX gonads [Chassot et al, 2012]. RSPO1/WNT4/ CTNNB1 signals have been shown to antagonize the masculinizing factors SOX9 and FGF9 downstream of Sry [Kim et al, 2006;Hiramatsu et al, 2009;Jameson et al, 2012;Nicol and Yao, 2015]. In addition to a partial sex reversal in either Wnt4 or Rspo1 mutant gonads [Vainio et al, 1999;Jeays-Ward et al, 2003;Jordan et al, 2003;Chassot et al, 2008;Tomizuka et al, 2008], ectopic expression of a stabilized form of CTNNB1 is sufficient to induce male-to-female sex reversal in XY gonads [Maatouk et al, 2008].…”
Section: Initial Molecular and Cellular Events In Ovarian Differentiamentioning
confidence: 99%